Recent Updates in Neurosurgical Interventions for Spontaneous Intracerebral Hemorrhage: Minimally Invasive Surgery to Improve Surgical Performance - Kobata, Hitoshi; Ikeda, Naokado (Frontiers in Neurology, 2021)
The efficacy and safety of surgical treatment for intracerebral hemorrhage (ICH) have long been subjects of investigation and debate. The recent results of the minimally invasive surgery plus alteplase for intracerebral hemorrhage evacuation (MISTIE) III trial demonstrated the safety of the procedure and a reduction in mortality. Although no improvement in functional outcomes was shown, the trial elucidated that benefits of intervention depend on surgical performance, with a greater ICH reduction, defined as ≤15 mL end of treatment ICH volume or ≥70% volume reduction, correlated with significant functional improvement. Recent meta-analyses indicated the benefits of neurosurgical hematoma evacuation, especially when performed earlier and done using minimally invasive procedures. In MISTIE III, to confirm absence of ICH growth and repeat alteplase administration, the mean time from onset to surgery and treatment completion took 47 and 123 h, respectively. Theoretically, the earlier the hematoma is removed, the better the outcome. A higher rate of hematoma reduction within an earlier time course may contribute to better outcomes. Neuroendoscopic surgery enables non-invasive removal of ICH under direct visualization. Minimally invasive procedures have continued to evolve with the support of advanced guidance systems and devices in favor of better surgical performance. Ongoing randomized controlled trials utilizing emerging minimally invasive techniques, such as the Early Minimally Invasive Removal of Intra Cerebral Hemorrhage (ENRICH) trial, Minimally Invasive Endoscopic Surgical Treatment with Apollo/Artemis in Patients with Brain Hemorrhage (INVEST) trial, and the Dutch Intracerebral Hemorrhage Surgery Trial (DIST), may provide significant information on the optimal treatment for ICH.